1995
DOI: 10.2165/00019053-199507020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development Costs for New Drugs by Therapeutic Category

Abstract: The clinical period (i.e. clinical trial and long term animal testing) development costs of a random sample of new chemical entities (NCEs) were examined for differences in average cost. All of the NCEs studied were first tested in humans between 1970 and 1982, and were classified for the purposes of the study by therapeutic class. The costs of unsuccessful projects were included with those of projects that resulted in US marketing approval. Including income forgone from expending funds before returns are earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(61 citation statements)
references
References 3 publications
0
60
1
Order By: Relevance
“…For an earlier period, DiMasi et al (1995a) found varying average clinical period costs for a number of major therapeutic classes. We will examine costs by therapeutic category in future research.…”
Section: Discussionmentioning
confidence: 99%
“…For an earlier period, DiMasi et al (1995a) found varying average clinical period costs for a number of major therapeutic classes. We will examine costs by therapeutic category in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The methodological approach used in this paper follows that used for our previous studies, although we apply additional statistical tests to the data (Hansen, 1979;DiMasi et al, 1991DiMasi et al, , 1995aDiMasi et al, ,b, 2003DiMasi et al, , 2004DiMasi and Grabowski, 2007). Because the methodologies are consistent, we can confidently make comparisons of the results in this study to the estimates we found for the earlier studies, which covered earlier periods, to examine and illustrate trends in development costs.…”
Section: Introductionmentioning
confidence: 91%
“…Title and abstract screening eliminated all but 24 of these citations. Most other citations were excluded at this stage because they were not on topic (1651 citations), they were commentaries (19), or they did not provide original estimates of the cost of drug development (22). Two additional, potentially relevant published articles were found through screening of references.…”
Section: Included Studiesmentioning
confidence: 99%